The correct answer of the given expression above would be the last option. We just solved this using the distributive property.
So: <span>(a - 3)(a - 5)
a^2 -3a -5a + 15
a^2 -8a + 15
Hope this is the answer that you are looking for. Have a great day!</span>
5a(b-c)=d. Here, we are trying to isolate the variable b.
Divide both sides by 5a: b-c=d/(5a)
Add c to both sides: b=
Answer:
B. 11 2/3
Step-by-step explanation:
c = 5 5/6*2
Change the mixed number to an improper fraction
5 5/6 = (6*5+5)/6 = (30+5)/6 = 35/6
c = 35/6 *2
c = 35/6 *2/1
= 70/6
Now we change it back to a mixed number
6 goes into 70 11 times
11*6 = 66 with 4 left over
11 4/6
We can simplify 4/6 by dividing the top and bottom by 2
11 2/3